2019
DOI: 10.3390/cancers11040584
|View full text |Cite
|
Sign up to set email alerts
|

Differential Activation of ERK Signaling in HPV-Related Oropharyngeal Squamous Cell Carcinoma

Abstract: Human papillomavirus (HPV)-related oropharyngeal squamous cell carcinoma (OPSCC) forms a distinct tumor entity with better survival clinical outcome. Numerous underlying molecular mechanisms have been postulated for differences in treatment response, but the impact of MEK/ERK signaling, a main driver of carcinogenesis in various cancers including OPSCC and key player mediating therapy resistance remains elusive. In a retrospective experimental cohort study, primary tumor samples from OPSCC patients (n = 124) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 58 publications
4
8
0
Order By: Relevance
“…As expected, the MAP kinase cascade (ERK/MEK/MAPK), a well-recognized target for HPV oncogenes [ 61 , 62 ], was also identified upstream of invasion-associated transcriptome perturbations ( Figure 12 ). The genes involved in this pathway represent quite specific modulators of angiogenesis, invasion and immune response.…”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…As expected, the MAP kinase cascade (ERK/MEK/MAPK), a well-recognized target for HPV oncogenes [ 61 , 62 ], was also identified upstream of invasion-associated transcriptome perturbations ( Figure 12 ). The genes involved in this pathway represent quite specific modulators of angiogenesis, invasion and immune response.…”
Section: Resultssupporting
confidence: 61%
“…At the same time, IL1RN (inhibitor of IL1 signaling), DKK1 (inhibitor of WNT signaling), and proto-cadherin PCDH18 (inhibitor of EMT and invasion) showed decreased expression. As expected, the MAP kinase cascade (ERK/MEK/MAPK), a well-recognized target for HPV oncogenes [61,62], was also identified upstream of invasion-associated transcriptome perturbations ( Figure 12). The genes involved in this pathway represent quite specific modulators of angiogenesis, invasion and immune response.…”
Section: Pathway Analysissupporting
confidence: 72%
See 1 more Smart Citation
“…4D). Another biomarker that is upregulated in HPV-positive cancers is phospho-extracellular signal-regulated kinase (pERK), the active form of the effector ERK for mitogen-activated protein kinase (MAPK) signaling (48,49). Levels of pERK were elevated in our MmuPV1-induced tongue tumors, compared to those in mock-infected tongues (Fig.…”
Section: Development Of An Mmupv1 Oral Infection Model In Immunodeficmentioning
confidence: 87%
“…However, the underlying molecular mechanism remains unknown. It has been reported that the NF‐kB and the ERK MAPK signaling pathways play an important role in the invasion and metastasis of cancers 16‐19 . Hence, western blotting was carried out to preliminarily test the molecular changes in NF‐kB and the ERK MAPK signaling pathways.…”
Section: Resultsmentioning
confidence: 99%